PERANCANGAN PURWARUPA SISTEM PENGATUR SUHU DAN KELEMBABAN KUMBUNG JAMUR OTOMATIS BERBASIS IOT DI KEBUN OKA JAMUR BALI - Natha Kusuma, I Putu; Setiawan, I Nyoman; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 12 No 1 (2025): Jurnal SPEKTRUM, 2025)
Oka Mushroom Farm Bali, located in Penarungan Village, Mengwi District, Badung Regency, is an oyster mushroom farm that faces the problem of maintaining the ideal temperature and humidity in the mushroom barn. This requires the farmers to regularly check and adjust the temperature and humidity conditions in the mushroom barn. In this study, a prototype of an automatic temperature and humidity monitoring system based on the Internet of Things (IoT) was designed as a control system to manage and control the temperature and humidity parameters in the mushroom barn environment. Based on the results of the prototype of the automatic temperature and humidity control system, the system is able to measure the environmental conditions of the mushroom barn, with humidity measurement results in the range of 79% - 82%, and the average temperature during the test reached 28.20°C. Using the monitoring system on a sample of 12 sacks in the mushroom house, an increase in yield of 22 grams or 5.6% was obtained compared to the traditional method.